2020
DOI: 10.1111/evo.13948
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of autotomy in leaf‐footed bugs

Abstract: Sacrificing body parts is one of many behaviors that animals use to escape predation. This trait, termed autotomy, is classically associated with lizards. However, several other taxa also autotomize, and this trait has independently evolved multiple times throughout Animalia. Despite having multiple origins and being an iconic antipredatory trait, much remains unknown about the evolution of autotomy. Here, we combine morphological, behavioral, and genomic data to investigate the evolution of autotomy within le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 82 publications
3
52
1
Order By: Relevance
“…To investigate our hypotheses, we used a subclade of leaf‐footed bugs for which there is an existing phylogenetic hypothesis, body size measurements, and autotomy data (data from Emberts et al., 2020). We specifically selected this subclade because we had access to almost every species that was represented in the phylogeny ( n = 26 species; Figure 2) and our previous knowledge suggested that this clade captures the diversity of flight/defense revealing states observed throughout the larger leaf‐footed bug clade.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate our hypotheses, we used a subclade of leaf‐footed bugs for which there is an existing phylogenetic hypothesis, body size measurements, and autotomy data (data from Emberts et al., 2020). We specifically selected this subclade because we had access to almost every species that was represented in the phylogeny ( n = 26 species; Figure 2) and our previous knowledge suggested that this clade captures the diversity of flight/defense revealing states observed throughout the larger leaf‐footed bug clade.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this study, we pruned the 62‐tip leaf‐footed bug phylogeny from Emberts et al. (2020), which was built from a concatenated alignment of 567 loci (Emberts et al., 2020, Figure 2). The phylogenetic reconstruction in Emberts et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations